Digital Business Implementation for the Development of Basreng and Sus Kering Snack Sales through Instagram and Shopee in Samarinda City: Penerapan Bisnis Digital untuk Pengembangan Penjualan Snack Basreng dan Sus Kering melalui Instagram dan Shopee di Kota Samarinda - Reza, Andi; Hasudungan, Rofilde; Ilham, Muhammad Fauzan Nur; Andromeda, Radhitya; Yahya, Alan; Rudiman (Journal of Empowerment and Community Service (JECSR), 2023)
The implementation of digital business has become a key strategy to enhance the competitiveness and sales of MSME products, particularly in the snack sector such as Basreng and Sus Kering in Samarinda City. This community service activity aims to develop product marketing through the utilization of digital platforms Instagram and Shopee. The methods applied include designing product visual identity, creating promotional content, and collaborating with MSME actors in packaging and product distribution processes. The results show that Instagram is effective in building brand awareness and consumer engagement, while Shopee facilitates transactions and expands market reach. The digital business implementation is also supported by the use of supporting applications such as Canva for promotional design. In conclusion, digital marketing strategies can increase exposure and sales of MSME products, providing innovative solutions to conventional marketing challenges.